A COMPARATIVE ANALYSIS: SELF-ACTUALIZATION PERSPECTIVES TOWARD “LELAKI YANG MENDERITA BILA DIPUJI” AND “BELALANG YANG SUKA BERGUNJING DAN TUJUH LEBAH MADU” - Dewi Christa Kobis; Devina Angelina Rantung (Unit Pengembangan Bahasa UIN Sayyid Ali Rahmatullah Tulungagung, 2023)
This study conducted a comparative analysis between “Lelaki yang menderita bila dipuji” and “Belalang yang suka bergunjing dan tujuh lebah madu”. It aimed to find out the similarities and differences between these two literary works and how these works were able to convey the perspectives of self-actualization. This is a qualitative method and implemented the theory by Abraham Maslow that focused on hierarchy of needs and self-actualization in analysing the data through the texts or the scripts. The findings showed that the two literary works that had been objects of this study showed similarities and differences for the physiological, safety, love, esteem, and even self-actualization needs. Each literary work might offered various style or uniqueness. However, they still portrayed a spot of similarity to each other especially in conveying moral lesson and Indonesian culture and behaviour such as respecting or being polite to each other and praising others sincerely without being envious. In addition, these two literary works showed that the fulfilment of self-actualization is important for human being and literary works were able to portray it properly.